From duplicity to the double: reading the upside down embroidery in José Eduardo Agualusa’s - doi: 10.4025/actascilangcult.v34i1.8389 - Knop, Rita Maria; Costa, Virgínia Carvalho de Assis (Acta Scientiarum. Language and Culture, 2011)
Doubleness and duplicity in the novel The Book of Chameleons by the Angolan writer Jose Eduardo Agualusa are analyzed. The two factors may be found in the identification between the two narrators and in the two most emphasized possibilities in the interpretation of the novel, or rather, subjectivity and national identity. Agualusa’s novel may also be defined as belonging to ‘minor literature’, as conceived by Deleuze and Guattari’s text Kafka: Toward a minor literature. According to these authors, in minor literature, each subject is inscribed in and connected with politics, a highly strong factor in The Book of Chameleons. ﻿